Correlation between Certain Complications and Health Education Program among Non-Insulin Dependent Diabetes Miletus Patients - Almola, Hammad Fadl; Hamed, Riyadh (International Journal of Medical and Health Sciences Research, 2015)
Background: A total of 150 diabetic patients were selected retrospectively from Khartoum State Diabetic Care Centers, this group divided to two equal groups, had been analyzed using the certain complications of non-insulin dependent diabetes mellitus patients after implementation of health education program. Group (cases) the program was implemented and the other group was considered as a control (75 patients for each group). Objective: The aim of the study to evaluate the correlation between the Health education program and complications among non-insulin dependent diabetes Miletus patients. Results: Reveals that the controls & intervention group had the same basic knowledge about DM complications at pre-test. Knowledge relevant to complications of DM was improved as a result of educational program in the intervention group in the immediately post-test. The level of knowledge were shown some decline in follow up test after 15 months the level of knowledge were significantly higher than the pre-test program another had, significant differences between intervention & control group was found. Shows foot care practiced among the studied patients before and after the program and after 15months of the program. Practicing good foot care was not done by a high percentage of our studied patients before program intervention. The most common practiced was washing the feet daily (46.7%). The least practiced foot care was asking the doctors for food exam (6.7 %), then management of minor foot complications (8.00%). Immediately after the program, there significant improvement was observed in the practices of foot care, as started to avoid activities that injure the feet, washed their feet daily, and chooses footwear (78.7%, 88%, and 65.3% respectively). Statistically significant was found between both groups (intervention and control) regarding foot care practiced compound to pre-program. Conclusion: In this study population, the Health education program of non-insulin dependent diabetes Miletus patients its relation diabetic complication determined.